2021
DOI: 10.1186/s13073-021-00857-3
|View full text |Cite
|
Sign up to set email alerts
|

Editing GWAS: experimental approaches to dissect and exploit disease-associated genetic variation

Abstract: Genome-wide association studies (GWAS) have uncovered thousands of genetic variants that influence risk for human diseases and traits. Yet understanding the mechanisms by which these genetic variants, mainly noncoding, have an impact on associated diseases and traits remains a significant hurdle. In this review, we discuss emerging experimental approaches that are being applied for functional studies of causal variants and translational advances from GWAS findings to disease prevention and treatment. We highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 147 publications
0
28
0
Order By: Relevance
“…Consistently, clinical trials targeting IL-1β in UC pancolitis are currently in progress today [49]. Functional genetics could substantially facilitate the assessment of clinical implication of IBD-associated genetic variation, thus contributing to the urging need for redefining of this entity [50,51]; hopefully, these latter have been the topics of two recently published studies [52,53].…”
Section: Discussionmentioning
confidence: 96%
“…Consistently, clinical trials targeting IL-1β in UC pancolitis are currently in progress today [49]. Functional genetics could substantially facilitate the assessment of clinical implication of IBD-associated genetic variation, thus contributing to the urging need for redefining of this entity [50,51]; hopefully, these latter have been the topics of two recently published studies [52,53].…”
Section: Discussionmentioning
confidence: 96%
“…The field of genetics as applied to complex traits has started to move beyond the identification of genetic associations and toward the elucidation of the mechanisms through which genetic variants confer risk (34, 35). However, a significant impediment to accomplishing this task is the fact that a strength GWAS studies, which leverage LD to identify regions conferring genetic risk, is also a weakness, in that the SNPs that tag genetic risk loci are in LD with dozens, sometimes hundreds, of other SNPs, most of which have no influence at all on disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation to this approach is the fact that MPRA may not detect effects as they would occur in native chromatin (35, 39). This limitation may lead to both false positives and false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of GWAS reports on variants found in intergenic and intronic regions, limiting their interpretability [15 52]. Identifying a gene from the variant(s) in GWAS necessitates additional evidence such as physical distances between the variants and the transcript start site, the location of regulatory regions (e.g., enhancers, chromatin), and other factors [38]. In fact, with over 1100 loci with leading SNPs, the transcriptome-wide summary statistics-based Mendelian randomization (TWMR) method [39] showed that 71% of the genes closest to that SNP do not show significant association with the tested phenotype.…”
Section: Discussionmentioning
confidence: 99%